2015
DOI: 10.1007/978-1-4471-6681-8_12
|View full text |Cite
|
Sign up to set email alerts
|

Play Platforms for Children’s Creativity

Abstract: Like Fröbel, Maria Montessori highlighted the importance of using objects and actively engaging in exploring the environment. Montessori's method, based on the Didactic Materials, addressed the stimulation of every sense (Montessori, 1912), and the design principle behind each of the objects from the Didactic Materials set, was to raise children's interest and curiosity. 2.1. Digital Manipulatives Recent technological developments made it possible to embed computational technology in objects, creating a new in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Whilst it is beyond the scope of this paper to give a detailed description of the development process, in the following section we will briefly present some relevant insights that informed the design of the final interface. For more information the reader may refer to [3].…”
Section: Digital Manipulatives For Playful Learning-the Case Of Tokmentioning
confidence: 99%
See 1 more Smart Citation
“…Whilst it is beyond the scope of this paper to give a detailed description of the development process, in the following section we will briefly present some relevant insights that informed the design of the final interface. For more information the reader may refer to [3].…”
Section: Digital Manipulatives For Playful Learning-the Case Of Tokmentioning
confidence: 99%
“…The study was structured in two main phases: the first one was dedicated to the design and implementation of the interface, and extended for a period of three years, involving six pre-school classes (ages five) and six preschool teachers [3]. Following the implementation, the researchers carried out three interventions at preschool for a period of around one year.…”
Section: Introductionmentioning
confidence: 99%
“…Initial studies carried out with paper cards with drawings representing story elements and an A4 sheet of paper, simulating a system for creating stories, have shown that the children tended to place all the cards filling the sheet of paper (Sylla et al, 2015); follow up studies carried out with an electronic prototype with six slots for placing blocks representing story elements, showed that children wished to create longer stories in which they could use more story elements than it was possible with the prototype. From these observations we concluded that ideally a system would not offer too many possibilities so that children would not feel pressured to use all of them nor should it be too limited.…”
Section: Untangling the Complexity Of Designing The Mobeybou Materialsmentioning
confidence: 99%
“…Aspects that have been investigated include the design of playful interactions focusing on learning [17,26], storytelling [11,8,12], dynamic systems [27], collaboration [23,25], or the learning of social skills [15] among others. Children's contributions and experiences in co-design activities [19,20,18,24], as well as reflections on roles and values of children in design [22] have also been topics of interest. Antle et al's Tangible Learning Design Framework (TLDF), is an example of a tool developed to support the design of TUIs [1,2] taking into account child development [3].…”
Section: Introductionmentioning
confidence: 99%